Comparison of methods of morcellation: manual versus power. (19th October 2015) - Moawad, Gaby N.; Abi KhalIL, Elias D.; Opoku‐Anane, Jessica; Marfori, Cherie Q.; Harman, Alice C.; Fisher, Steven; Levy, Matt; Robinson, James K.
Abstract: Introduction: With the growing controversy surrounding power morcellation (PM), other approaches must be examined so that women may still benefit from minimally invasive gynecologic surgeries. In this study we sought to compare power morcellation to manual morcellation through mini‐laparotomy or vaginally. Materials and Methods: Retrospective cohort study carried out at an urban teaching hospital including 274 women who underwent a minimally invasive myomectomy or hysterectomy, requiring morcellation for tissue extraction. Surgical outcomes were compared between PM, manual morcellation through mini‐laparotomy (MMM) and manual morcellation through the vagina (MMV). Primary outcome measured was operative time. Secondary outcomes were intraoperative and postoperative complications. Results: Compared with PM, MMM was associated with shorter operative time for hysterectomy, (140.5 min vs. 164.2 min, p  = 0.05). Intraoperative and postoperative complications were similar among groups. There were four postoperative complications in the MMV group, one related to blood transfusion and three related to postoperative vaginal cuff and pelvic infections. Conclusion: Compared with PM, MMM is associated with shorter operative time during hysterectomies. Intraoperative and postoperative complications were similar among groups.